Analisis Tindak Tutur Asertif dalam Film Jangkrik Boss! - Ni Kadek Ayu Sintya Dewi; I Wayan Pastika; I Wayan Simpen (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Assertive speech acts are one type of speech act that is important in communication. Research using assertive speech act analysis can help to understand the information, beliefs and opinions of speakers properly and correctly. Assertive speech acts can be found in various types of communication, for example in a film. Therefore, this research will find and analyze assertive speech acts in one of the famous comedy films entitled Jangkrik Boss!. This research aims to find, study and analyze assertive illocutionary speech acts in the film Jangkrik Boss! so that the meaning contained in the film's speech is interpreted correctly based on the context of the speech. The data used in this research are qualitative data and quantitative data. This data was obtained using data collection methods and techniques, namely the listening method with advanced methods of free, skillful, involved listening and supported by note-taking techniques. The data analysis methods and techniques used are pragmatic matching methods and contextual methods supported by basic techniques for selecting determining elements and advanced techniques of comparing comparisons. The methods and techniques for presenting the results of data analysis used are formal and informal methods supported by formative techniques. In this research, thirty utterances were found that used assertive illocutionary speech acts. These assertive speech acts consist of stating, complaining, affirming, and mentioning. Based on the analysis that has been carried out, it is known that assertive illocutionary in films is used to express opinions, complaints and information conveyed by actors in the film.